(untitled) (KULT_online, 2011)
Daniel Grinsted, graduate of Cultural Studies and Anglistics/Americanistics, published Die Reise zum Mond (Trip to the Moon), a short monograph about the phenomenon of fictitious and real explorations of the moon. He focuses on reconstructing the medial history of moon observations and moon travels, from the first usage of telescopes to fun-fair attractions in lunar parks as well as to the moon landing in 1969. In spite of some interesting observations, this study is no ’giant leap for mankind’.